Secondary Schools and Teenage Childbearing : Evidence from the School Expansion in Brazilian Municipalities - Koppensteiner, Martin Foureaux (World Bank, Washington, DC, 2020)
This article investigates the effect increasing secondary education opportunities has on teenage fertility in Brazil. Using a novel dataset to exploit variation from a 57 increase in secondary schools across 4,884 Brazilian municipalities between 1997 and 2009, the analysis shows an important role of secondary school availability on underage fertility. An increase of one school per 100 females reduces a cohort's teenage birthrate by between 0.250 and 0.563 births per 100, or a reduction of one birth for roughly every 50 to 100 students who enroll in secondary education. The results highlight the important role of access to education leading to spillovers beyond improving educational attainment.